The effectiveness of the "Olweus Bully Prevention Program" among schools' students: An experimental study conducted on a middle school in Al Ain city, United Arab Emirates - Abdulaziz Albrithen (Journal of Umm Al-Qura University for Social Sciences, 2022)
The problem of bullying among school children is an old phenomenon. Although bullying is an old problem, it was scientifically addressed only in the 1970s. During the past two decades there were many worldwide researches try to address the nature of bullying, and reveal the extent of the phenomenon, its causes and effects. One of the earliest empirical researches was a study conducted by the psychologist at the University of Bergen, Norway, "Dan Olweus" who able to formulate an integrated treatment program to deal with the school bullying. Due to the impressive successes achieved by that program in reducing the problem of school bullying, large-scale studies have attempted to measure the impact of the program or verify its effectiveness. All of these studies have found compelling evidence of the effectiveness of the Olweus Bully Prevention Program (OBPP). This study attempts to test the program on the United Arab Emirates, and to verify the feasibility of the program in reducing or preventing the problem of school bullying within the Arab culture. The general result was that the program was effective in reducing bullying at school, and this important result was evidenced by the quantitative and qualitative data of the current study.